2018
DOI: 10.1186/s40798-018-0119-2
|View full text |Cite
|
Sign up to set email alerts
|

Safety in Mixed Martial Arts: a 7-Year Review of Cancelled MMA Bouts in Calgary, Alberta, During the Pre-bout Medical Examination Period

Abstract: BackgroundPresently, there is no literature that examines the reasons for the cancellation of amateur or professional mixed martial arts (MMA) bouts. The purpose of this study was to review the circumstances that lead to the cancellation of MMA bouts by Calgary ringside physicians during the pre-bout examination period and to identify any emerging patterns that may guide the regulatoin of this sport.MethodsThe case-series  was constructed from the Calgary Combative Sports Commission pre-bout examination record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…One study showed that orbital fractures were a cause of prebout cancellation due to chronic orbital fracture with fat prolapse seen on CT imaging. 25 Visual compromise or persistent diplopia could also factor into an athlete's ability to fight.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that orbital fractures were a cause of prebout cancellation due to chronic orbital fracture with fat prolapse seen on CT imaging. 25 Visual compromise or persistent diplopia could also factor into an athlete's ability to fight.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 27 reported on the pre-bout medical screening of MMA athletes and identified 5.8% of athletes with medical reasons for termination of their bout. In this cohort, the most common reason for the match cancellation was abnormal neuroimaging, including post-traumatic gliosis, mircohaemorrhage, chronic orbital fractures and lacunar infarct.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring standardised precontest medical screening prevents unsuitable athletes from participating in competition, exacerbating an existing health concern or creating a new health issue. Curran-Sills 27 outlined several recommendations that included: the creation of guidelines regarding pre-bout and post-bout neuroimaging, the implementation of industry-wide minimum medical screening standards, the adoption of a longitudinal approach for weight monitoring and the development of competent ringside physician groups. Within the MMA community, there appears to be interest and will to implement some of these approaches to optimise MMA athlete health and reduce the risk of poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analysis showed that in MMA head trauma is a serious problem—repeated mild traumatic brain injury may cause chronic traumatic encephalopathy and impaired cognitive functions [ 9 ]. Curran-Sills et al [ 10 ] recommended that there should be guidelines created regarding pre- and post-bout neuroimaging, standard medical screening introduced, the development of competent ringside physician groups, and active oversight by the Combative Sports Commission during the matchmaking process. There have been associations made between head injuries in MMA and potential risk factors such as age, sex, weight, match outcome and bout length.…”
Section: Introductionmentioning
confidence: 99%